2017
DOI: 10.1007/s13312-018-1319-z
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary Dysplasia in Preterm Neonates in a Level III Neonatal Unit in India

Abstract: Chorioamnionitis, PDA and sepsis were significantly associated with BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…to 50%, likely because of differences in gestational age or birth weight criteria for confirmed a BPD diagnosis [5][6][7][8][9][10]. A multicenter retrospective analysis from China showed that the incidence of BPD decreases with increase in gestational age and weight [11], which is consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 80%
“…to 50%, likely because of differences in gestational age or birth weight criteria for confirmed a BPD diagnosis [5][6][7][8][9][10]. A multicenter retrospective analysis from China showed that the incidence of BPD decreases with increase in gestational age and weight [11], which is consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 80%
“…EPICure 2 study [4] showed nearly 60% of babies ≤26 weeks had BPD. Studies from India [20,21] reported an incidence of BPD of 28.7%, 10.7% & 11.2% in infants less than 28 weeks, 29-30 weeks and 31-32 weeks respectively The BPD rates from Indian centre in this study is lower than reported studies from India. Necrotising enterocolitis ≥stage 2 is 11.5% and 12.6% in U.K and Indian cohort, results are comparable to the previous studies [23].Number of babies with severe Retinopathy of Prematurity (ROP) and number of ROP needing treatment with laser or Avastin was signi cantly higher in Indian centre (12.9% vs 7.7%) despite higher gestational age of cohort than the UK centre possibly explained by difference in practices or higher risk factors.…”
Section: Discussioncontrasting
confidence: 71%
“…This low incidence may be because of inclusion of moderate preterm infants in the study, exclusion of infants with gestation <25 weeks and increased overall mortality. Bhunwal et al 19 reported almost similar incidence (11.2%) of infants requiring oxygen for ≥28 days among the infants with gestation <33 weeks and requiring respiratory support in the first 3 days of life. De Campos Bannwart et al 8 developed two predicting models for LOS in infants with very low birth weight.…”
Section: Discussionmentioning
confidence: 88%
“…Apart from the weight and gestational age at birth, in our study, many other antenatal factors (doppler abnormalities, severe SGA status at birth) and neonatal morbidities (need for resuscitation, RDS, seizures, sepsis, NEC, major malformations and BPD) independently influenced hospital duration (Tables 5 and 6). Among the perinatal factors, severe SGA status had the highest influence on LOS with an increase of 21 (19)(20)(21)(22)(23) days. As foetal growth restriction is more common in developing countries like India, severe SGA status at birth should be considered as an important factor in influencing the LOS.…”
Section: Discussionmentioning
confidence: 99%